Evidence of Asymptomatic Visual Losses after Surgical Repair of Cerebral Aneurysm - Bastos, Albedy Moreira; Rodrigues, Anderson Raiol; Côrtes, Maria Izabel Tentes; Lacerda, Eliza Maria da Costa Brito; Lima, Mônica Gomes; Teixeira, Cláudio Eduardo Corrêa; Silveira, Luiz Carlos de Lima (Frontiers in Neurology, 2017)
Deficits in visual acuity, visual field and oculomotor function are commonly detected after repair of cerebral aneurysms. However, when these deficits are absent, it does not mean that other potential visual losses also are absent. Here, we report three cases that after complete recover from surgical repair of cerebral aneurysms presented minimal visual acuities of about 20/20 and no visual disturbances. While two of them (cases 1 and 2) showed visual fields with no relevant central defects, two of them showed relevant impairments in spatial contrast sensitivity (cases 2 and 3). This evidences that after complete recover from surgical repair of hemorrhagic cerebral aneurysms spatial contrast sensitivity can be asymptomatically impaired when visual acuity (cases 2 and 3) and visual fields (case 2) are not correlated with symptoms of visual disturbances. Hypothetical explanations and consequences of such evidence are discussed.